Dampak Adiksi Pornografi Terhadap Kehidupan Sosial Remaja - Sifa Salsabila; Resti Okta Sari (JUDIKA: Jurnal Pendidikan dan Bahasa, 2023)
Adolescence is a phase of life that all humans will definitely pass through. This phase is very important because during adolescence a person will search for their own identity. Apart from that, the current condition of teenagers will influence the conditions when teenagers approach adulthood and play an active role in productive life and social life in society. Today's technological developments are very sophisticated and easy to access, one of which is access to pornographic films which are very easily accessed by teenagers which results in addiction to watching pornographic films repeatedly and will affect their social life behavior when interacting in the community such as not being able to socialize because they are closed and not confident and in the school environment teenagers will have difficulty concentrating on studying and will be alone away from their friends because of their lack of self-confidence. The method used in this research is the observation method, namely a data collection technique carried out through observations, accompanied by notes on the condition or behavior of the target object. Many teenagers have girlfriends at a very young age and even hold hands easily in society because the films they watch are not appropriate for their age, which makes them curious in the phase of finding their identity. The aim of this research is to find out how teenagers behave regarding the impact of pornography addiction. The results of this research show that many teenagers behave negatively and begin to imitate sexual acts towards anyone. Keywords: Pornography, Teenagers, Social Life